Effects of rumen-protected methionine supplementation on the performance of high production dairy cows in the tropics. - Valdir Chiogna Junior; Fernanda Lopes; Charles George Schwab; Mateus Zucato Toledo; Edgar Alain Collao-Saenz (PLoS ONE)
Increasing methionine availability in dairy cow diets during the first third of lactation may enhance their performance and health. The aim of this study was to determine the effect of supplementing rumen-protected methionine (Smartamine® M, SM) in a lactation diet with protein and energy levels calculated according to the literature. Seventy-six multiparous Holstein cows (39.1 ± 6.8 kg of milk/d and 65 ± 28 DIM) were assigned to 1 of 2 dietary treatments (38/treatment) according to a randomized complete block design with a 2-wk (covariate) and 10-wk experimental period. Treatments were a basal diet (CON; 3.77 Lys:1Met); and CON + 23 g SM (2.97 Lys:1 Met). Individual milk samples were taken every 2 weeks to determine milk composition. Blood was collected from 24 cows on d+30 d to measure plasma AA levels. Body weight and body condition score (BCS) were measured at the beginning and the end of the experiment. The SM diet promoted higher milk yield (41.7 vs. 40.1 kg/d; P = 0.03). Energy-corrected milk yield (41.0 vs. 38.0 kg/d), milk protein yield (1.30 vs. 1.18 kg/d), milk protein (3.14% vs. 2.97%) and casein (2.39% vs. 2.28%) were also different (P < 0.01) as well as milk fat yield (1.42 vs. 1.29 kg/d; P = 0.02). A trend (P = 0.06) for higher milk fat % (3.41% vs. 3.21%) was observed. Both diets resulted in similar body weight, but CON-fed cows tended (P = 0.08) to have higher BCS. Higher plasma methionine levels were determined with SM compared with CON (29.6 vs. 18.4 μM; P < 0.01), but lysine and histidine were not different. Dietary supplementation of RPM improved productive performance by increasing milk yield and milk components yields, suggesting better dietary AA utilization when Met levels are adjusted in Lys-adequate lactation diets.